STUDENTS’ PERCEPTION OF GOOGLE CLASSROOM ON ONLINE LEARNING OF ENGLISH EDUCATION STUDY PROGRAM AT BATURAJA UNIVERSITY - Henny Yulia (Journal of Language Education (JoLE), 2022)
This study aims to find out what is the students’ perception of Google Classroom on online learning of English education study program at Baturaja University. This study used descriptive quantitative method. The population of this research was 91 students of English education study program. The researcher only took 73 students namely the 4th, 6th and 8th semester as the sample by applying purposive sampling. The data was collected through the questionnaire with Google form as an intermediary application. It consists of 16 statements. Then the researcher used five points of Likert Scale for analyzing the data based on percentage interval and Google form. The result of this research was students had positive response and support Google Classroom as learning media in online learning. It showed that Google Classroom is an effective tool for online learning because it can help the students to improve their learning through an active participation and Google Classroom is an easy tool to use and learning because of its features and it can access anywhere and make save time.